Deciphering pretreatment-induced repartition among stratified extracellular biopolymers and its effect on anaerobic biodegradability and dewaterability of waste activated sludge. Issue 3 (June 2017) - Lü, Fan; Wang, Fang; Shao, Liming; He, Pinjing
Graphical abstract: Highlights: All pretreatments improved solubilization of the sludge. Solubilization degree didn't correspond to anaerobic biodegradability. Excessive release of biopolymers deteriorated the dewaterability. FTIR and SERS revealed the key role of tightly-bound EPS. SERS were effective to probe the minor changes in EPS after pretreatment. Abstract: The effectiveness and optimization strategy of various pretreatment methods to enhance the anaerobic biodegradability and dewaterability of waste activated sludge are still inconclusive. In order to explore the intrinsic triggers determining the apparent biodegradability and dewaterability, sludges pretreated by freeze-thawing, acid, alkali, sonication, thermal autoclaving, and ultraviolet radiation were fractionized according to the cohesion of extracellular polymeric substances (EPS). The fractionized EPS and cells were characterized for microscopic properties by biochemical and elemental composition, Fourier transform infrared spectroscopy, and surface-enhanced Raman spectroscopy. Multivariate statistical analysis was used to mining the key microscopic factors affecting the apparent biodegradability or dewaterability of sludge. Results show that, solubilization degree significantly determined the dewaterability of the pretreated sludge, but did not affect the biodegradability. The properties of slime and lightly-bound EPS were different from other fractions, and inclined to be altered by various pretreatments. However, only the H content, H/C ratio and some functional groups of tightly-bound EPS have significant correlation with the ultimate methane production yield, while the N/C ratio of lightly-bound EPS was important for the initial methane production rate. Free-thawing improved sludge's biodegradability and dewaterability through dehydration in micro-zones. Autoclaving and ultraviolet weakened sludge's biodegradability and dewaterability by accelerating the denaturation of some collagen proteins in tightly-bound EPS, transforming it into a viscous gel-like network with higher water-holding capacity. Sonication acted similarly but at a micro-zone level. Acid and alkali pretreatments improved biodegradability by accelerating the release of cell endocytes including pigments carotene and carotenoids.